1996
DOI: 10.1086/176775
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Oscillation of Radiative Shock Waves in Accretion Disks around Compact Objects

Abstract: We extend our previous numerical simulation of accretion disks with shock waves when cooling e ects are also included. We consider bremsstrahlung and other power law processes: / T 2 to mimic cooling in our simulation. We employ Smoothed Particle Hydrodynamics technique as in the past. We observe that for a given angular momentum of the ow, the shock wave undergoes a steady,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
278
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(288 citation statements)
references
References 17 publications
6
278
0
Order By: Relevance
“…While it has been reported that QPOs can also be generated by cooling (Molteni et al 1996b). In realistic disc, both processes are active, and both should produce shock oscillation.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 97%
See 2 more Smart Citations
“…While it has been reported that QPOs can also be generated by cooling (Molteni et al 1996b). In realistic disc, both processes are active, and both should produce shock oscillation.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 97%
“…Hot electrons in the post-shock region, abbreviated as CENBOL (CENtrifugal pressure supported Boundary Layer), may explain the power-law tail of the spectrum from black hole candidates in hard states, while a weak or no shock solution produces a dearth of hot electrons which may cause the weaker power-law tail in the soft states (Chakrabarti & Titarchuk 1995;Mandal & Chakrabarti 2010). Moreover, a large number of authors have shown the formation of bipolar outflows from the post-shock accretion flow, both numerically (Molteni et al 1994(Molteni et al , 1996b as well as analytically (Le & Becker 2005;Chattopadhyay & Das 2007;Fukumura & Kazanas 2007;Das & Chattopadhyay 2008;Das et al 2009;Kumar et al , 2014. It is also interesting to note that, by considering a simplified inviscid accretion, and which has the right parameters to form a standing shock, Das et al (2001) qualitatively showed that there would be no jets in no-shock or weak shock condition of the disc, or in other words, when the disc is in the soft spectral state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown previously that accretion disc shock may launch bipolar jets (Molteni et al 1994(Molteni et al , 1996aDas et al 2014;Lee et al 2016). The jump condition across an accretion shock is obtained by conserving fluxes across the shock front, e.g., mass flux, momentum flux and energy flux (Taub 1948).…”
Section: Shock Waves In Accretion and Bipolar Jetsmentioning
confidence: 99%
“…This formalism has been used previously by Mondal et al (2009). Though we use the QPO frequency to be equal to the inverse of infall time, as found in Molteni et al (1996b), this relation need not be strictly followed (see also Das 2003 andSukova &Janiuk 2015). pointed out that the resonance condition could be satisfied over a wide band of parameter range.…”
Section: Estimation Of α During Outbursts Of Various Sourcesmentioning
confidence: 99%